2018
DOI: 10.3389/fnhum.2018.00024
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Tasking in Multiple Sclerosis – Implications for a Cognitive Screening Instrument

Abstract: The monitoring of cognitive functions is central to the assessment and consecutive management of multiple sclerosis (MS). Though, especially cognitive processes that are central to everyday behavior like dual-tasking are often neglected. We examined dual-task performance using a psychological-refractory period (PRP) task in N = 21 patients and healthy controls and conducted standard neuropsychological tests. In dual-tasking, MS patients committed more erroneous responses when dual-tasking was difficult. In eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 82 publications
0
26
0
1
Order By: Relevance
“…In addition, cognitive assessment performed in a ‘sterilized’ way, might not reflect cognitive issues of patients since they might perform well in tests highly specific to a single cognitive domain, but fail in multitasking real conditions [ 95 ]. Studies have shown that walking or other motor tasks might interfere with cognitive function in MS patients [ 96 , 97 ], therefore dual-tasking measures may better reflect actual difficulties of MS patients [ 98 ].…”
Section: When To Measure and How To Deal With Findings?mentioning
confidence: 99%
“…In addition, cognitive assessment performed in a ‘sterilized’ way, might not reflect cognitive issues of patients since they might perform well in tests highly specific to a single cognitive domain, but fail in multitasking real conditions [ 95 ]. Studies have shown that walking or other motor tasks might interfere with cognitive function in MS patients [ 96 , 97 ], therefore dual-tasking measures may better reflect actual difficulties of MS patients [ 98 ].…”
Section: When To Measure and How To Deal With Findings?mentioning
confidence: 99%
“…This is of high relevance because there are strong links between the sNfl and the integrity of the white matter structure ( 30 34 ), particularly in MS ( 35 , 36 ). It has been shown ( 37 ) that MS patients performed considerably worse than healthy control participants and that the deficits shown by the patients are very likely not due to simple motor deficits.…”
Section: Cognitive–cognitive Dual Tasking Assessment In the Context Omentioning
confidence: 99%
“…This is furthermore the case because dual-tasking tests (like the PRP) require the responses to be simple visual digits/letters and tones, making it possible to create parallel versions of the task easily and quickly without changing the task difficulty or other characteristics of the test. Data examining the PRP in MS have shown that variations in motor speed (e.g., due to MS-related motor disturbances) do not represent a confound in this task because mostly the accuracy to respond seems to be modulated in MS ( 37 ). Moreover, a PRP task can also be applied using voice responses ( 41 ).…”
Section: Cognitive–cognitive Dual Tasking Assessment In the Context Omentioning
confidence: 99%
“…Yet, in the field of MS-research, dual-tasking has mostly been examined by assessing the performance of simple cognitive tasks while walking [24][25][26][27][28][29] or balancing [30,31]. These approaches, focusing on cognition-motor interactions [29], however, bear the problem that task difficulty is not parametrically scalable, and are thus possibly unsuitable to detect early dysfunctions and track disease progression [32]. Moreover, the assessment is not easily controllable [33].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these issues, a previous study by our group introduced the usage of dual-task to examine the above-mentioned abilities in MS patients [32]. This test is based on a so-called psychological refractory period (PRP) task.…”
Section: Introductionmentioning
confidence: 99%